A heat dissipation type carbon fiber battery back cover and preparation method thereof

By using modified nanocarbon fiber and polycarbonate materials in the battery back cover, the problem of easy damage and insufficient heat dissipation performance of the battery back cover of portable electronic equipment during use is solved, and high impact resistance and good heat dissipation effects are achieved.

CN119039755BActive Publication Date: 2025-04-11HUIZHOU ZONGSHENG ELECTRONICS MATERIAL CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411007079.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-25
Publication Date
2025-04-11
Estimated Expiration
2044-07-25

AI Technical Summary

Technical Problem

The battery cover of existing portable electronic equipment is easily damaged due to falling or heating during use, and it is difficult to meet the needs of excellent drop resistance and good heat dissipation.

Method used

Polycarbonate is used as the resin substrate and modified nanocarbon fibers are used as the reinforcement material. The dispersion and thermal conductivity of nanocarbon fibers in the resin are improved through the modification treatment to form a heat-dissipating carbon fiber battery back cover.

Benefits of technology

It achieves high impact resistance and good heat dissipation performance of the battery back cover, avoids equipment damage caused by heat accumulation, and improves the service life and safety of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of battery back covers, and specifically to a heat-dissipating carbon fiber battery back cover and a preparation method thereof. In order to improve the impact resistance and heat dissipation performance of the battery back cover, the present invention uses polycarbonate as a resin substrate, and uses modified nano-carbon fibers as a reinforcing material therein, and introduces aromatic benzene rings and fluorine elements on the surface of the nano-carbon fibers to improve the wear resistance of the material. On this basis, a polycarbonate-like structure is further introduced on the surface of the nano-carbon fibers to improve the compatibility with the polycarbonate resin, thereby enhancing the impact resistance of the composite material. The nano-carbon fibers also have excellent thermal conductivity, which can achieve rapid heat conduction, avoid heat accumulation during use of electronic equipment, and achieve the purpose of rapid heat conduction and heat dissipation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery back covers, and in particular to a heat dissipation type carbon fiber battery back cover and a preparation method thereof. Background Art

[0002] With the rapid development of electronic products, various intelligent devices have gradually spread to every corner of human life, and various electronic terminals have become an important part of human life;

[0003] At present, most portable electronic terminals require battery power to operate the device. However, portable electronic devices are often inevitably damaged during use, such as falling, which often poses a huge challenge to the safety performance of the battery. In addition, during use, the heat caused by the operation of the device is often reflected in various portable electronic devices. Therefore, it is necessary to develop a battery back cover with excellent drop resistance and good heat dissipation performance to meet market-related needs. Summary of the invention

[0004] The object of the present invention is to provide a heat dissipation type carbon fiber battery back cover and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a heat dissipation type carbon fiber battery back cover, comprising the following steps:

[0006] S1. Preparation of modified carbon nanofibers;

[0007] S11. Disperse the nanocarbon fibers in a mixed solution of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:1, heat to 95±5°C, stir to react for 2~4h, filter out the carbon fibers, wash the carbon fibers with hydrochloric acid solution and deionized water for 3~5 times, disperse the carbon fibers again in deionized water, add sodium hydroxide and monochloroacetic acid, heat to 45~60°C, stir to react for 2~4h, take out, wash with deionized water for 5~8 times, and dry to obtain carboxylated nanocarbon fibers;

[0008] S12. Disperse triphenylpropionic acid in dimethyl sulfoxide, heat to 65-75°C, stir and disperse for 30-90 minutes, add 2,3,5,6-tetrafluoro-4-mercaptobenzoic acid and 1,3-diisopropylcarbodiimide, heat to 180-183°C, stir and reflux for 4-8 hours, cool to room temperature, and drop the reaction solution into dimethyl sulfoxide containing 2,4,6-triaminopyrimidine for 1-5 hours. After the dropwise addition is completed, heat to 75-85°C, stir and react for 2-4 hours, and then remove excess solvent by rotary evaporation to obtain an amino-terminated intermediate;

[0009] S13. The amino-terminated intermediate is dispersed in DMF, heated to 75-80°C, stirred and mixed for 30-45 minutes, and then carboxylated nano-carbon fibers are added. After ultrasonic vibration reaction for 2-10 hours, the precipitation is separated by centrifugation. After washing the surface with DMF, the precipitation is dispersed in xylene again, ultrasonic vibration treatment for 30-45 minutes, biphenyl dicarboxylic acid is added, heated to 87-95°C, stirred and reacted for 1-5 hours, and the precipitation is separated by centrifugation. The precipitation is dispersed in bisphenol A again, heated to 75-85°C, stirred and reacted for 2-4 hours, and then the precipitation is separated by centrifugation. After washing with toluene 2-3 times, vacuum drying is performed to constant weight to obtain bisphenol A modified nano-carbon fibers;

[0010] S14. Under a nitrogen atmosphere, dichloromethane was cooled to -20~-15°C, bisphenol A modified nanocarbon fibers were added, and after ultrasonic dispersion for 30~45min, solid phosgene was added, and after stirring until completely dissolved, sodium hydroxide was added, and the reaction was continued with stirring for 15~30min, and the precipitate was separated by centrifugation, washed with ethanol for 3~5 times, and vacuum dried to constant weight to obtain modified nanocarbon fibers;

[0011] S2. Mix polycarbonate, ABS resin and modified nano-carbon fiber, raise the temperature to 265-270°C, mix evenly, and then perform injection molding at a pressure of 150-180 MPa. After cooling and demolding, a heat-dissipating carbon fiber battery back cover is obtained.

[0012] Furthermore, in step S11, the mass ratio of the nano-carbon fibers, sodium hydroxide and monochloroacetic acid is 5: (3-6): (2.5-5).

[0013] Furthermore, in step S12, the mass ratio of triphenylpropionic acid, 2,3,5,6-tetrafluoro-4-mercaptobenzoic acid, and 1,3-diisopropylcarbodiimide is 10: (6.5-7.5): (0.05-0.1).

[0014] Furthermore, in step S12, the mass ratio of triphenylpropionic acid to 2,4,6-triaminopyrimidine is 10:(3.2-4.2).

[0015] Furthermore, in step S13, the mass ratio of the carboxylated carbon nanofibers, the amino-terminated intermediate, biphenyl dicarboxylic acid, and bisphenol A is 10: (0.5-4): (1-2.5): (2-6).

[0016] Furthermore, in step S14, the mass ratio of the dichloromethane, bisphenol A modified carbon nanofiber, solid phosgene, and sodium hydroxide is (500-1000):10:(10-25):(10-20).

[0017] Furthermore, in step S2, the heat dissipation type carbon fiber battery back cover is composed of 50-60 parts of polycarbonate, 15-25 parts of ABS resin, and 15-25 parts of modified nano-carbon fiber, by weight.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] In order to improve the impact resistance and heat dissipation performance of the battery back cover, the present invention uses polycarbonate as a resin substrate and uses nano carbon fibers as a reinforcing material therein, thereby enhancing the impact resistance of the composite material. The nano carbon fibers also have excellent thermal conductivity, which can achieve rapid heat conduction, avoid heat accumulation during the use of electronic equipment, and achieve the purpose of rapid heat conduction and heat dissipation.

[0020] In order to further improve the dispersion of nano-carbon fibers in the resin material, the present invention also performs a modification treatment on the nano-carbon fibers;

[0021] The invention first oxidizes the surface of the nano-carbon fiber, and then introduces a carboxyl group on the surface of the nano-carbon fiber under the action of monochloroacetic acid and sodium hydroxide; then, the invention also uses triphenylpropionic acid as a raw material, reacts it with 2,3,5,6-tetrafluoro-4-mercaptobenzoic acid and 2,4,6-triaminopyrimidine, so as to prepare an amino-terminated intermediate containing a large number of aromatic benzene ring structures, and reacts the amino-terminated intermediate with the nano-carbon fiber with a carboxyl group, so as to introduce an aromatic benzene ring on the surface of the nano-carbon fiber. The introduction of the aromatic benzene ring can further improve the rigidity of the resin material and enhance the wear resistance of the material, and the carbon atoms in the aromatic benzene ring are mutually combined with adjacent carbon atoms through σ bonds to form a strong molecular skeleton, wherein the π electrons move freely on the ring to form an electron cloud, thereby generating a strong electron conjugation effect, thereby enhancing the conductivity of the electrons and facilitating the conduction of heat;

[0022] On this basis, the present invention further uses biphenyl dicarboxylic acid and bisphenol A to treat nano-carbon fibers, thereby grafting and introducing a bisphenol A structure on the surface of the nano-carbon fibers, and then reacting it with phosgene to generate a polycarbonate-like structure on the surface of the nano-carbon fibers, thereby effectively improving the dispersion and compatibility of the fibers in the polycarbonate substrate and improving the mechanical properties of the material. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] The nano carbon fiber used in this application has a fiber diameter of 150-200 nm, a length of 10-20 μm, and a thermal conductivity of 2000 W / m; the ABS resin used is PA-757F ABS resin; the polycarbonate used is Makrolon Rx2530 polycarbonate;

[0025] Embodiment 1. A method for preparing a heat dissipation type carbon fiber battery back cover, comprising the following steps:

[0026] S1. Preparation of modified carbon nanofibers;

[0027] S11. Disperse 5 parts of nano-carbon fiber in a mixed solution of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:1 by weight, heat to 95°C, stir to react for 3 hours, filter out the carbon fiber, wash the carbon fiber with hydrochloric acid solution and deionized water 5 times, disperse the carbon fiber again in deionized water, add 3 parts of sodium hydroxide and 2.5 parts of monochloroacetic acid, heat to 60°C, stir to react for 3 hours, take out, wash with deionized water 5 times, and dry to obtain carboxylated nano-carbon fiber;

[0028] S12. Disperse 10 parts of triphenylpropionic acid in dimethyl sulfoxide by weight, heat to 70°C, stir and disperse for 75 minutes, add 6.5 parts of 2,3,5,6-tetrafluoro-4-mercaptobenzoic acid and 0.1 parts of 1,3-diisopropylcarbodiimide, heat to 181°C, stir and reflux for 6 hours, cool to room temperature, and drop the reaction solution into dimethyl sulfoxide containing 3.2 parts of 2,4,6-triaminopyrimidine for 4 hours. After the addition is completed, heat to 80°C, stir and react for 3 hours, and then remove excess solvent by rotary evaporation to obtain an amino-terminated intermediate;

[0029] S13. Disperse 0.5 parts of the terminal amino intermediate in DMF by weight, heat to 75°C, stir and mix for 30 minutes, add 10 parts of carboxylated nano-carbon fibers, react by ultrasonic vibration for 8 hours, centrifuge and separate the precipitate, wash the surface with DMF, disperse the precipitate again in xylene, ultrasonically shake for 30 minutes, add 1 part of biphenyl dicarboxylic acid, heat to 87°C, stir and react for 4 hours, centrifuge and separate the precipitate, disperse the precipitate again in 2 parts of bisphenol A, heat to 75°C, stir and react for 3 hours, centrifuge and separate the precipitate, wash with toluene 3 times, and vacuum dry to constant weight to obtain bisphenol A modified nano-carbon fibers;

[0030] S14. By weight, 500 parts of dichloromethane were cooled to -20 ° C under a nitrogen atmosphere, 10 parts of bisphenol A modified nanocarbon fibers were added, and after ultrasonic dispersion for 30 minutes, 10 parts of solid phosgene were added, and after stirring until completely dissolved, 10 parts of sodium hydroxide were added, and the reaction was continued with stirring for 15 minutes, and the precipitate was separated by centrifugation, washed with ethanol 5 times, and vacuum dried to constant weight to obtain modified nanocarbon fibers;

[0031] S2. By weight, 50 parts of polycarbonate, 15 parts of ABS resin, and 15 parts of modified nano-carbon fiber are mixed, the temperature is raised to 270°C, the mixing is uniform, and then injection molding is performed at a pressure of 180 MPa. After cooling and demolding, a heat-dissipating carbon fiber battery back cover is obtained.

[0032] Embodiment 2. A method for preparing a heat dissipation type carbon fiber battery back cover, comprising the following steps:

[0033] Compared with Example 1, this embodiment increases the amount of 2,3,5,6-tetrafluoro-4-mercaptobenzoic acid added in step S12;

[0034] S1. Preparation of modified carbon nanofibers;

[0035] S11. Disperse 5 parts of nano-carbon fiber in a mixed solution of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:1 by weight, heat to 95°C, stir to react for 3 hours, filter out the carbon fiber, wash the carbon fiber with hydrochloric acid solution and deionized water 5 times, disperse the carbon fiber again in deionized water, add 3 parts of sodium hydroxide and 2.5 parts of monochloroacetic acid, heat to 60°C, stir to react for 3 hours, take out, wash with deionized water 5 times, and dry to obtain carboxylated nano-carbon fiber;

[0036] S12. Disperse 10 parts of triphenylpropionic acid in dimethyl sulfoxide by weight, heat to 70°C, stir and disperse for 75 minutes, add 7.5 parts of 2,3,5,6-tetrafluoro-4-mercaptobenzoic acid and 0.1 parts of 1,3-diisopropylcarbodiimide, heat to 181°C, stir and reflux for 6 hours, cool to room temperature, and drop the reaction solution into dimethyl sulfoxide containing 3.2 parts of 2,4,6-triaminopyrimidine for 4 hours. After the addition is completed, heat to 80°C, stir and react for 3 hours, and then remove excess solvent by rotary evaporation to obtain an amino-terminated intermediate;

[0037] S13. Disperse 0.5 parts of the terminal amino intermediate in DMF by weight, heat to 75°C, stir and mix for 30 minutes, add 10 parts of carboxylated nano-carbon fibers, react by ultrasonic vibration for 8 hours, centrifuge and separate the precipitate, wash the surface with DMF, disperse the precipitate again in xylene, ultrasonically shake for 30 minutes, add 1 part of biphenyl dicarboxylic acid, heat to 87°C, stir and react for 4 hours, centrifuge and separate the precipitate, disperse the precipitate again in 2 parts of bisphenol A, heat to 75°C, stir and react for 3 hours, centrifuge and separate the precipitate, wash with toluene 3 times, and vacuum dry to constant weight to obtain bisphenol A modified nano-carbon fibers;

[0038] S14. By weight, 500 parts of dichloromethane were cooled to -20 ° C under a nitrogen atmosphere, 10 parts of bisphenol A modified nanocarbon fibers were added, and after ultrasonic dispersion for 30 minutes, 10 parts of solid phosgene were added, and after stirring until completely dissolved, 10 parts of sodium hydroxide were added, and the reaction was continued with stirring for 15 minutes, and the precipitate was separated by centrifugation, washed with ethanol 5 times, and vacuum dried to constant weight to obtain modified nanocarbon fibers;

[0039] S2. By weight, 50 parts of polycarbonate, 15 parts of ABS resin, and 15 parts of modified nano-carbon fiber are mixed, the temperature is raised to 270°C, the mixing is uniform, and then injection molding is performed at a pressure of 180 MPa. After cooling and demolding, a heat-dissipating carbon fiber battery back cover is obtained.

[0040] Embodiment 3. A method for preparing a heat dissipation type carbon fiber battery back cover, comprising the following steps:

[0041] Compared with Example 1, this example increases the amount of the amino-terminated intermediate added in step S13;

[0042] S1. Preparation of modified carbon nanofibers;

[0043] S11. Disperse 5 parts of nano-carbon fiber in a mixed solution of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:1 by weight, heat to 95°C, stir to react for 3 hours, filter out the carbon fiber, wash the carbon fiber with hydrochloric acid solution and deionized water 5 times, disperse the carbon fiber again in deionized water, add 3 parts of sodium hydroxide and 2.5 parts of monochloroacetic acid, heat to 60°C, stir to react for 3 hours, take out, wash with deionized water 5 times, and dry to obtain carboxylated nano-carbon fiber;

[0044] S12. Disperse 10 parts of triphenylpropionic acid in dimethyl sulfoxide by weight, heat to 70°C, stir and disperse for 75 minutes, add 6.5 parts of 2,3,5,6-tetrafluoro-4-mercaptobenzoic acid and 0.1 parts of 1,3-diisopropylcarbodiimide, heat to 181°C, stir and reflux for 6 hours, cool to room temperature, and drop the reaction solution into dimethyl sulfoxide containing 3.2 parts of 2,4,6-triaminopyrimidine for 4 hours. After the addition is completed, heat to 80°C, stir and react for 3 hours, and then remove excess solvent by rotary evaporation to obtain an amino-terminated intermediate;

[0045] S13. Disperse 4 parts of the amino-terminated intermediate in DMF by weight, heat to 75°C, stir and mix for 30 minutes, add 10 parts of carboxylated carbon nanofibers, react by ultrasonic vibration for 8 hours, centrifuge and separate the precipitate, wash the surface with DMF, disperse the precipitate again in xylene, ultrasonically shake for 30 minutes, add 1 part of biphenyl dicarboxylic acid, heat to 87°C, stir and react for 4 hours, centrifuge and separate the precipitate, disperse the precipitate again in 2 parts of bisphenol A, heat to 75°C, stir and react for 3 hours, centrifuge and separate the precipitate, wash with toluene 3 times, and vacuum dry to constant weight to obtain bisphenol A modified carbon nanofibers;

[0046] S14. By weight, 500 parts of dichloromethane were cooled to -20 ° C under a nitrogen atmosphere, 10 parts of bisphenol A modified nanocarbon fibers were added, and after ultrasonic dispersion for 30 minutes, 10 parts of solid phosgene were added, and after stirring until completely dissolved, 10 parts of sodium hydroxide were added, and the reaction was continued with stirring for 15 minutes, and the precipitate was separated by centrifugation, washed with ethanol 5 times, and vacuum dried to constant weight to obtain modified nanocarbon fibers;

[0047] S2. By weight, 50 parts of polycarbonate, 15 parts of ABS resin, and 15 parts of modified nano-carbon fiber are mixed, the temperature is raised to 270°C, the mixing is uniform, and then injection molding is performed at a pressure of 180 MPa. After cooling and demolding, a heat-dissipating carbon fiber battery back cover is obtained.

[0048] Embodiment 4. A method for preparing a heat dissipation type carbon fiber battery back cover, comprising the following steps:

[0049] Compared with Example 1, this embodiment increases the amount of solid phosgene added in step S14;

[0050] S1. Preparation of modified carbon nanofibers;

[0051] S11. Disperse 5 parts of nano-carbon fiber in a mixed solution of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:1 by weight, heat to 95°C, stir to react for 3 hours, filter out the carbon fiber, wash the carbon fiber with hydrochloric acid solution and deionized water 5 times, disperse the carbon fiber again in deionized water, add 3 parts of sodium hydroxide and 2.5 parts of monochloroacetic acid, heat to 60°C, stir to react for 3 hours, take out, wash with deionized water 5 times, and dry to obtain carboxylated nano-carbon fiber;

[0052] S12. Disperse 10 parts of triphenylpropionic acid in dimethyl sulfoxide by weight, heat to 70°C, stir and disperse for 75 minutes, add 6.5 parts of 2,3,5,6-tetrafluoro-4-mercaptobenzoic acid and 0.1 parts of 1,3-diisopropylcarbodiimide, heat to 181°C, stir and reflux for 6 hours, cool to room temperature, and drop the reaction solution into dimethyl sulfoxide containing 3.2 parts of 2,4,6-triaminopyrimidine for 4 hours. After the addition is completed, heat to 80°C, stir and react for 3 hours, and then remove excess solvent by rotary evaporation to obtain an amino-terminated intermediate;

[0053] S13. Disperse 0.5 parts of the terminal amino intermediate in DMF by weight, heat to 75°C, stir and mix for 30 minutes, add 10 parts of carboxylated nano-carbon fibers, react by ultrasonic vibration for 8 hours, centrifuge and separate the precipitate, wash the surface with DMF, disperse the precipitate again in xylene, ultrasonically shake for 30 minutes, add 1 part of biphenyl dicarboxylic acid, heat to 87°C, stir and react for 4 hours, centrifuge and separate the precipitate, disperse the precipitate again in 2 parts of bisphenol A, heat to 75°C, stir and react for 3 hours, centrifuge and separate the precipitate, wash with toluene 3 times, and vacuum dry to constant weight to obtain bisphenol A modified nano-carbon fibers;

[0054] S14. By weight, 500 parts of dichloromethane were cooled to -20 ° C under a nitrogen atmosphere, 10 parts of bisphenol A modified nanocarbon fibers were added, and after ultrasonic dispersion for 30 minutes, 25 parts of solid phosgene were added, and after stirring until completely dissolved, 10 parts of sodium hydroxide were added, and the reaction was continued with stirring for 15 minutes, and the precipitate was separated by centrifugation, washed with ethanol 5 times, and vacuum dried to constant weight to obtain modified nanocarbon fibers;

[0055] S2. By weight, 50 parts of polycarbonate, 15 parts of ABS resin, and 15 parts of modified nano-carbon fiber are mixed, the temperature is raised to 270°C, the mixing is uniform, and then injection molding is performed at a pressure of 180 MPa. After cooling and demolding, a heat-dissipating carbon fiber battery back cover is obtained.

[0056] Example 5. A method for preparing a heat dissipation type carbon fiber battery back cover, comprising the following steps:

[0057] Compared with Example 1, this embodiment increases the amount of modified carbon nanofiber added in step S2;

[0058] S1. Preparation of modified carbon nanofibers;

[0059] S11. Disperse 5 parts of nano-carbon fiber in a mixed solution of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:1 by weight, heat to 95°C, stir to react for 3 hours, filter out the carbon fiber, wash the carbon fiber with hydrochloric acid solution and deionized water 5 times, disperse the carbon fiber again in deionized water, add 3 parts of sodium hydroxide and 2.5 parts of monochloroacetic acid, heat to 60°C, stir to react for 3 hours, take out, wash with deionized water 5 times, and dry to obtain carboxylated nano-carbon fiber;

[0060] S12. Disperse 10 parts of triphenylpropionic acid in dimethyl sulfoxide by weight, heat to 70°C, stir and disperse for 75 minutes, add 6.5 parts of 2,3,5,6-tetrafluoro-4-mercaptobenzoic acid and 0.1 parts of 1,3-diisopropylcarbodiimide, heat to 181°C, stir and reflux for 6 hours, cool to room temperature, and drop the reaction solution into dimethyl sulfoxide containing 3.2 parts of 2,4,6-triaminopyrimidine for 4 hours. After the addition is completed, heat to 80°C, stir and react for 3 hours, and then remove excess solvent by rotary evaporation to obtain an amino-terminated intermediate;

[0061] S13. Disperse 0.5 parts of the terminal amino intermediate in DMF by weight, heat to 75°C, stir and mix for 30 minutes, add 10 parts of carboxylated nano-carbon fibers, react by ultrasonic vibration for 8 hours, centrifuge and separate the precipitate, wash the surface with DMF, disperse the precipitate again in xylene, ultrasonically shake for 30 minutes, add 1 part of biphenyl dicarboxylic acid, heat to 87°C, stir and react for 4 hours, centrifuge and separate the precipitate, disperse the precipitate again in 2 parts of bisphenol A, heat to 75°C, stir and react for 3 hours, centrifuge and separate the precipitate, wash with toluene 3 times, and vacuum dry to constant weight to obtain bisphenol A modified nano-carbon fibers;

[0062] S14. By weight, 500 parts of dichloromethane were cooled to -20 ° C under a nitrogen atmosphere, 10 parts of bisphenol A modified nanocarbon fibers were added, and after ultrasonic dispersion for 30 minutes, 10 parts of solid phosgene were added, and after stirring until completely dissolved, 10 parts of sodium hydroxide were added, and the reaction was continued with stirring for 15 minutes, and the precipitate was separated by centrifugation, washed with ethanol 5 times, and vacuum dried to constant weight to obtain modified nanocarbon fibers;

[0063] S2. According to weight percentage, 50 parts of polycarbonate, 15 parts of ABS resin, and 25 parts of modified nano-carbon fiber are mixed, the temperature is raised to 270°C, and after mixing evenly, injection molding is performed at a pressure of 180MPa. After cooling and demolding, a heat-dissipating carbon fiber battery back cover is obtained.

[0064] Comparative Example 1. A method for preparing a heat dissipation type carbon fiber battery back cover, comprising the following steps:

[0065] Compared with Example 1, the modified carbon nanofiber was not prepared in this comparative example;

[0066] S1. According to weight percentage, 50 parts of polycarbonate, 15 parts of ABS resin, and 15 parts of modified nano-carbon fiber are mixed, the temperature is raised to 270°C, and after mixing evenly, injection molding is performed at a pressure of 180MPa. After cooling and demolding, a heat dissipating carbon fiber battery back cover is obtained.

[0067] Comparative Example 2. A method for preparing a heat dissipation type carbon fiber battery back cover, comprising the following steps:

[0068] Compared with Example 1, this comparative example did not prepare the modified carbon nanofiber using the amino-terminated intermediate;

[0069] S1. Preparation of modified carbon nanofibers;

[0070] S11. Disperse 5 parts of nano-carbon fiber in a mixed solution of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:1 by weight, heat to 95°C, stir to react for 3 hours, filter out the carbon fiber, wash the carbon fiber with hydrochloric acid solution and deionized water 5 times, disperse the carbon fiber again in deionized water, add 3 parts of sodium hydroxide and 2.5 parts of monochloroacetic acid, heat to 60°C, stir to react for 3 hours, take out, wash with deionized water 5 times, and dry to obtain carboxylated nano-carbon fiber;

[0071] S12. Disperse 10 parts of carboxylated carbon nanofibers in xylene by weight, treat with ultrasonic vibration for 30 minutes, add 1 part of biphenyl dicarboxylic acid, heat to 87°C, stir to react for 4 hours, centrifuge to separate the precipitate, disperse the precipitate in 2 parts of bisphenol A again, heat to 75°C, stir to react for 3 hours, centrifuge to separate the precipitate, wash with toluene 3 times, and vacuum dry to constant weight to obtain bisphenol A modified carbon nanofibers;

[0072] S13. By weight, 500 parts of dichloromethane were cooled to -20 ° C under a nitrogen atmosphere, 10 parts of bisphenol A modified nanocarbon fibers were added, and after ultrasonic dispersion for 30 minutes, 10 parts of solid phosgene were added, and after stirring until completely dissolved, 10 parts of sodium hydroxide were added, and the reaction was continued with stirring for 15 minutes, and the precipitate was separated by centrifugation, washed with ethanol 5 times, and vacuum dried to constant weight to obtain modified nanocarbon fibers;

[0073] S2. By weight, 50 parts of polycarbonate, 15 parts of ABS resin, and 15 parts of modified nano-carbon fiber are mixed, the temperature is raised to 270°C, the mixing is uniform, and then injection molding is performed at a pressure of 180 MPa. After cooling and demolding, a heat-dissipating carbon fiber battery back cover is obtained.

[0074] Testing: The samples prepared in Example 1-2 of Example 1-5 were injection molded into strips.

[0075] The impact resistance is tested according to GB / T 1043-93;

[0076] Tensile properties test according to GB / T 1040.2-2006;

[0077] Using 0000# steel wool and a load of 1 kg, the surface of the sample prepared in Example 1-2 of Example 1-5 was rubbed to test its wear amount per unit time;

[0078] The thermal conductivity of the samples prepared in Examples 1-5 and Comparative Examples 1-2 was tested using a German NETZSCH xenon lamp thermal conductivity instrument LFA 447. The test results are shown in the following table.

[0079]

[0080] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a heat dissipation type carbon fiber battery back cover, characterized in that: The following steps are involved: S1. Preparation of modified carbon nanofibers; S11. Disperse the nanocarbon fibers in a mixed solution of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:1, heat to 95±5°C, stir to react for 2~4h, filter out the carbon fibers, wash the carbon fibers with hydrochloric acid solution and deionized water for 3~5 times, disperse the carbon fibers again in deionized water, add sodium hydroxide and monochloroacetic acid, heat to 45~60°C, stir to react for 2~4h, take out, wash with deionized water for 5~8 times, and dry to obtain carboxylated nanocarbon fibers; S12. Disperse triphenylpropionic acid in dimethyl sulfoxide, heat to 65-75°C, stir and disperse for 30-90 minutes, add 2,3,5,6-tetrafluoro-4-mercaptobenzoic acid and 1,3-diisopropylcarbodiimide, heat to 180-183°C, stir and reflux for 4-8 hours, cool to room temperature, and drop the reaction solution into dimethyl sulfoxide containing 2,4,6-triaminopyrimidine for 1-5 hours. After the dropwise addition is completed, heat to 75-85°C, stir and react for 2-4 hours, and then remove excess solvent by rotary evaporation to obtain an amino-terminated intermediate; S13. The amino-terminated intermediate is dispersed in DMF, heated to 75-80°C, stirred and mixed for 30-45 minutes, and then carboxylated nano-carbon fibers are added. After ultrasonic vibration reaction for 2-10 hours, the precipitation is separated by centrifugation. After washing the surface with DMF, the precipitation is dispersed in xylene again, ultrasonic vibration treatment for 30-45 minutes, biphenyl dicarboxylic acid is added, heated to 87-95°C, stirred and reacted for 1-5 hours, and the precipitation is separated by centrifugation. The precipitation is dispersed in bisphenol A again, heated to 75-85°C, stirred and reacted for 2-4 hours, and then the precipitation is separated by centrifugation. After washing with toluene 2-3 times, vacuum drying is performed to constant weight to obtain bisphenol A modified nano-carbon fibers; S14. Under a nitrogen atmosphere, dichloromethane was cooled to -20~-15°C, bisphenol A modified nanocarbon fibers were added, and after ultrasonic dispersion for 30~45min, solid phosgene was added, and after stirring until completely dissolved, sodium hydroxide was added, and the reaction was continued with stirring for 15~30min, and the precipitate was separated by centrifugation, washed with ethanol for 3~5 times, and vacuum dried to constant weight to obtain modified nanocarbon fibers; S2. Mix polycarbonate, ABS resin and modified nano-carbon fiber, raise the temperature to 265-270°C, mix evenly, and then perform injection molding at a pressure of 150-180 MPa. After cooling and demolding, a heat-dissipating carbon fiber battery back cover is obtained.

2. The method for preparing a heat dissipation type carbon fiber battery back cover according to claim 1, characterized in that: In step S11, the mass ratio of the nano-carbon fibers, sodium hydroxide and monochloroacetic acid is 5: (3-6): (2.5-5).

3. The method for preparing a heat dissipation type carbon fiber battery back cover according to claim 1, characterized in that: In step S12, the mass ratio of triphenylpropionic acid, 2,3,5,6-tetrafluoro-4-mercaptobenzoic acid, and 1,3-diisopropylcarbodiimide is 10: (6.5-7.5): (0.05-0.1).

4. The method for preparing a heat dissipation type carbon fiber battery back cover according to claim 1, characterized in that: In step S12, the mass ratio of triphenylpropionic acid to 2,4,6-triaminopyrimidine is 10:(3.2-4.2).

5. The method for preparing a heat dissipation type carbon fiber battery back cover according to claim 1, characterized in that: In step S13, the mass ratio of the carboxylated carbon nanofibers, the amino-terminated intermediate, biphenyl dicarboxylic acid, and bisphenol A is 10: (0.5-4): (1-2.5): (2-6).

6. The method for preparing a heat dissipation type carbon fiber battery back cover according to claim 1, characterized in that: In step S14, the mass ratio of the dichloromethane, bisphenol A modified carbon nanofiber, solid phosgene, and sodium hydroxide is (500-1000):10:(10-25):(10-20).

7. The method for preparing a heat dissipation type carbon fiber battery back cover according to claim 1, characterized in that: In step S2, the heat dissipation type carbon fiber battery back cover is composed of 50-60 parts of polycarbonate, 15-25 parts of ABS resin, and 15-25 parts of modified nano-carbon fiber, by weight.

8. A heat dissipating carbon fiber battery back cover prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Carbon fiber reinforced thermoplastic resin composite material with superior heat dissipation performance and preparation method

    CN104151805A

  • Composite material applicable to LED lamp radiators

    CN107828023A